International Transporter Consortium Commentary on Clinically Important Transporter Polymorphisms. Issue 1 (7th November 2012) - Giacomini, K M; Balimane, P V; Cho, S K; Eadon, M; Edeki, T; Hillgren, K M; Huang, S‐M; Sugiyama, Y; Weitz, D; Wen, Y; Xia, C Q; Yee, S W; et al.
<x xml:space="preserve">Abstract</x> This Commentary focuses on genetic polymorphisms in membrane transporters. We present two polymorphisms for which there is a compelling body of literature supporting their clinical relevance: OATP1B1 (c.521T>C, p.V174A, rs4149056) and BCRP (c.421C>A, p.Q141K, rs2231142). The clinical evidence demonstrating their role in variation in pharmacokinetics and pharmacodynamics is described along with their allele frequencies in ethnic populations. Recommendations for incorporating studies of transporter polymorphisms in drug development are provided, along with the regulatory implications. Clinical Pharmacology & Therapeutics (2013); 94 1, 23–26. doi:10.1038/clpt.2013.12